Motivational virtual training for people with disabilities in rural areas of Malaysia - Abdul Wahat, Nor Wahiza; A. Hamid, Tetty Ruziaty (Universiti Putra Malaysia Press, 2018)
Virtual training with its interactive and inclusive features is a very suitable psychological empowerment tool for people with disabilities in Malaysia's rural areas. Since the conduct of virtual supervision does not require any trainer or instructor to be physically present at the training premise, it is accessible for the usage of minority groups, who usually face the issue of mobility and accessibility. A session of virtual training involving 50 people with disabilities in Kota Kinabalu, Sabah was conducted for market validation of the virtual training. Post-training, the participants were interviewed to obtain their feedback on the virtual training in which they had participated. Overall findings from the interview showed that the participants had found the motivational virtual training to be relevant to them. The themes that emerged as the findings of the study are the conduciveness of virtual training for people with disabilities, modelling behaviour and error management. It has been found that virtual training could actually provide people with disabilities with the skill development and knowledge enhancement opportunities that lead to positive implications in their career development.